Factors Influencing Students’ Intention to Use E-learning Systems: A Systematic Literature Review - Alsubaie, Raghad; Shariff, Sya Azmeela; Ismail, Syuhaida; Masrom, Maslin (Advances in Social Sciences Research Journal, 2025)
Throughout the years, electronic learning (e-learning) systems have been transforming higher education nationwide and worldwide, particularly in educational institutions. In this context, there is a need for a systematic synthesis of a variety of technological, psychological, and socio-cultural aspects that determine the students’ intention to embrace e-learning. This study conducts a systematic literature review (SLR) using the Technology Acceptance Model (TAM) and its extensions, focusing on key factors such as self-efficacy, subject norms, enjoyment, experience, content quality, and computer anxiety. Additionally, it provides an argument that accessibility is a crucial but relatively less-studied moderator factor influencing e-learning adoption. The findings indicate that while numerous studies address infrastructure-related challenges, there is limited context-specific evidence regarding their impact on e-learning acceptance. This study contributes to the TAM literature and offers practical insights for enhancing digital learning initiatives in educational institutions.